2019
DOI: 10.3847/1538-4357/ab164d
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation in z ∼ 0.8 Quiescent Galaxies in LEGA-C

Abstract: We use reconstructed star-formation histories (SFHs) of quiescent galaxies at z = 0.6 − 1 in the LEGA-C survey to identify secondary star-formation episodes that, after an initial period of quiescence, moved the galaxies back to the star-forming main sequence (blue cloud). 16 ± 3% of the z ∼ 0.8 quiescent population has experienced such rejuvenation events in the redshift range 0.7 < z < 1.5 after reaching quiescence at some earlier time. On average, these galaxies first became quiescent at z = 1.2, and those … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 54 publications
6
43
1
Order By: Relevance
“…Recently, Pawlik et al (2018) found that 40 per cent of massive post-starburst galaxies in the local universe are the result of red sequence galaxies undergoing 'rejuvenation events' and moving towards the massive end of the red sequence through minor mergers. Such rejuvenation of ETGs has also been observed at z ∼ 0.8 by Chauke et al (2019). Works by the SAURON collaboration have found that ETGs can be divided in fast and slow rotators (Emsellem et al 2007) according to the prominence of their rotational component, a classification that has been linked to different formation processes (Cappellari et al 2011;Penoyre et al 2017;Smethurst et al 2018).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Recently, Pawlik et al (2018) found that 40 per cent of massive post-starburst galaxies in the local universe are the result of red sequence galaxies undergoing 'rejuvenation events' and moving towards the massive end of the red sequence through minor mergers. Such rejuvenation of ETGs has also been observed at z ∼ 0.8 by Chauke et al (2019). Works by the SAURON collaboration have found that ETGs can be divided in fast and slow rotators (Emsellem et al 2007) according to the prominence of their rotational component, a classification that has been linked to different formation processes (Cappellari et al 2011;Penoyre et al 2017;Smethurst et al 2018).…”
Section: Introductionmentioning
confidence: 70%
“…Therefore, at large masses, it is likely that the young components are the result of rejuvenation (e.g. Pawlik et al 2018;Chauke et al 2019) events triggered by minor mergers or cold gas accretion in previously quiescent systems. A merger-driven scenario is consistent with results by Kaviraj et al (2011), who find that ETGs at z ∼ 0.6 showing signs of recent starformation are more likely to exhibit disturbed morphologies reminiscent of recent minor mergers.…”
Section: Where Do Young Components Come From?mentioning
confidence: 99%
“…3). Finally, even rejuvenated QGs are typically identified as sub-MS (Chauke et al 2019;Mancini et al 2019). Model predictions might therefore substantially deviate from observations for galaxy populations where these processes play a significant role.…”
Section: Resultsmentioning
confidence: 95%
“…Due to requiring sensitivity to low-levels of star-formation from the UV emission, we limit our analysis in this section to galaxies at < 0.1. Note that this is a shorter-timescale rejuvenation selection than previous studies (see, e.g., Thomas et al 2010;Chauke et al 2019, for low-and high-redshift analyses respectively) which used spectral features to Figure 11. Histograms of stellar mass binned transient and star-forming galaxies with respect to / 180 .…”
Section: Rejuvenating Galaxiesmentioning
confidence: 98%